Seronegative Myasthenia Gravis and Graves’ Disease. Is there a link? - Polymeris, A.; Karoutsou, E.; Doumouchtsis, K. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Graves’ disease (GD) and myasthenia gravis (MG) are common autoimmune diseases but their coexistence is very rare. They may possibly share the same pathogenetic mechanisms. Recent research has shown the involvement of autoantibodies, lymphocytes, cytokines and chemokines in the pathogenesis of MG and GD. It appears that Th17 cell lineage is involved in autoimmune thyroid disease (AITD) and seems to be key factor in the development of both MG and GD.A 34-year-old male with seronegative myasthenia gravis due to thymic hyperplasia was diagnosed with also GD and opthalmopathy. Several diagnostic and therapeutic issues regarding the relevant literature are discussed.
Keywords: Graves-disease; Graves opthalmopathy; myasthenia Gravis; thymic hyperpalasia; periodic hypokalemic paralyis